The Agromyzidae (Diptera) of Greenland
1. Nine species of Agromyzidae (Diptera) are recorded from Greenland, of which two are described as new. The new species are Cerodontha (Dizygomyza) thulensis, described from Thule in the Northwest, and Phytomyza vibeana, a species closely related to the holarctic P. ranunculi (SCHRANK